The Defense Mechanism Of Raina Petkoff In George Bernard Shaw's Arms And The Man Play: A Psychoanalytic Approach - Hasim, Wakhid, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S. M. Hum (2015)
The study is about how defense mechanism is reflected in George Bernard Shaw's Arm and the Man. The purpose of this study is to analyze the major's character personality based on the structural elements and the psychoanalytic perspective of Sigmund Freud. In analyzing Arms and the Man, the researcher uses the psychoanalytic approach and qualitative method. This research has several benefits to give additional information which is can be used by the other literature researchers who interested to analyze this play. This study is using two data sources, primary and secondary data source. The primary data source is the manuscript of the play, and the secondary data are taken from some information needed. The method of data collection is qualitative research. For the last, the researcher makes an analysis of Raina's character using defense mechanism. The analysis is started by analyzing his Id, Ego, Superego, anxiety and then her defense mechanism. The analysis of the previous chapter brings this study into following conclusions. First, based on the structural analysis, it can be concluded that within the play George Bernard Shaw explains that there is a clear differentiator between idea and reality. Second, based on the psychoanalytic analysis it shows the anxiety caused conflicts between Id, Ego, and Superego in the major character produce defense mechanism.